PENGARUH KONSENTRASI NUTRISI AB MIX DAN SETEK BIBIT YANG BERBEDA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MINT (Mentha piperita L.) PADA HIDROPONIK SISTEM DFT - Wahyuni, Endang Sri (JURNAL BIOSHELL, 2023)
This study aims to determine the effect of different nutrient concentrations of AB mix and seed cuttings on the growth and production of mint plants in the DFT hydroponic system. This research was conducted at the Greenhouse of the Faculty of Agriculture, Jember Islamic University from July to September 2019. The research method used was a factorial Completely Randomized Design (CRD), consisting of 2 factors. The first factor is the cutting material consisting of shoot cuttings (A1) and stems cuttings (A2) and the second factor is the concentration of AB mix nutrients consisting of 400-700 ppm (B1) and 500-800 ppm (B2). The results showed that the treatment of shoot cuttings (A1) resulted in the highest production and had a significantly different effect on the parameters of plant height and number of branches. While the concentration of AB mix 500-800 ppm (B2) resulted in the highest production and gave a significantly different effect on the parameters of the number of leaves, plant height, and plant wet weight. Keywords: DFT hydroponics, mint, nutrient concentration, seed cuttings.